224k views
0 votes
Using factor theorem, factorise x⁴-x³-7x²+x+6

2 Answers

3 votes

Answer:

Add and subtract the second term to the expression and factor by grouping .

(x-1)(x+1)(x-3)(x+2)

User Riga
by
5.3k points
5 votes

Answer:

(x-1)(x-3)(x+1)(x+2)

Explanation:

x⁴-x³-7x²+x+6=

x⁴-x³-x²+x -6x²+6=

x³(x-1)-x(x-1)-6(x²-1)=

x³(x-1)-x(x-1)-6(x-1)(x+1)=

(x-1)(x³-x-6x-6)=

(x-1)(x³-3x²+3x²-9x+2x-6)=

(x-1)(x-3)(x²+3x+2)=

(x-1)(x-3)(x²+x+2x+2)=

(x-1)(x-3)(x+1)(x+2)

User Segev
by
5.8k points